Assessing Chemical Heterogeneity at the Nanoscale in Mixed‐Ligand Metal–Organic Frameworks with the PTIR Technique1. (24th February 2014) - Katzenmeyer, Aaron M.; Canivet, Jerome; Holland, Glenn; Farrusseng, David; Centrone, Andrea
Abstract Recently, the use of mixtures of organic‐building‐block linkers has given chemists an additional degree of freedom for engineering metal–organic frameworks (MOFs) with specific properties; however, the poor characterization of the chemical complexity of such MixMOF structures by conventional techniques hinders the verification of rational design. Herein, we describe the application of a technique known as photothermal induced resonance to individual MixMOF microcrystals to elucidate their chemical composition with nanoscale resolution. Results show that MixMOFs isoreticular to In‐MIL‐68, obtained either directly from solution or by postsynthetic linker exchange, are homogeneous down to approximately 100 nm. Additionally, we report a novel in situ process that enables the engineering of anisotropic domains in MOF crystals with submicron linker‐concentration gradients.